Intermittent Fasting Promotes White Adipose Browning and Decreases Obesity by Shaping the Gut Microbiota - Li, Guolin; Xie, Cen; Lu, Siyu; Nichols, Robert G.; Tian, Yuan; Li, Licen; Patel, Daxeshkumar; Ma, Yinyan; Brocker, Chad N.; Yan, Tingting; Krausz, Kristopher W.; Xiang, Rong; et al. (Cell metabolism, 2017)
While activation of beige thermogenesis is a promising approach for treatment of obesity-associated diseases, there are currently no known pharmacological means of inducing beiging in humans. Intermittent fasting is an effective and natural strategy for weight control, but the mechanism for its efficacy is poorly understood. Here, we show that an every-other-day fasting (EODF) regimen selectively stimulates beige fat development within white adipose tissue and dramatically ameliorates obesity, insulin resistance, and hepatic steatosis. EODF treatment results in a shift in the gut microbiota composition leading to elevation of the fermentation products acetate and lactate and to the selective upregulation of monocarboxylate transporter 1 expression in beige cells. Microbiota-depleted mice are resistance to EODF-induced beiging, while transplantation of the microbiota from EODF-treated mice to microbiota-depleted mice activates beiging and improves metabolic homeostasis. These findings provide a new gut-microbiota-driven mechanism for activating adipose tissue browning and treating metabolic diseases. [Display omitted] •EODF is a novel strategy for beige adipose development•EODF selectively induces WAT beiging by reshaping gut microbiota•EODF reverses high-fat-diet-induced obesity and associated metabolic disorders•The microbiota-fat axis orchestrates EODF-induced metabolic improvement White adipose beiging is a promising therapy for obesity and related metabolic diseases. Here, Li, Xie and colleagues find that an EODF regimen can selectively induce the beiging of white adipose tissue and subsequently ameliorate metabolic disorders in mice. Gut microbiota orchestrate the effects of EODF on beiging and metabolic improvement.